1999
DOI: 10.1046/j.1365-2672.1999.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing bacterial resistance to antibiotics with ultrasound

Abstract: The effect of erythromycin on planktonic cultures of Pseudomonas aeruginosa, with and without application of 70 kHz ultrasound, was studied. Ultrasound was applied at levels that had no inhibitory effect on cultures of Ps. aeruginosa. Ultrasound in combination with erythromycin reduced the viability of Ps. aeruginosa by 1–2 orders of magnitude compared with antibiotic alone, even at concentrations below the minimum inhibitory concentration (MIC). Electron‐spin resonance studies suggest that ultrasound induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
2
29
0
2
Order By: Relevance
“…This would seemingly follow previous theories surrounding a charged EPS matrix [23,35] by suggesting that structural changes to the biofilm enhancing its susceptibility to antimicrobials are related to both mechanical and electrical characteristics. The way in which an electromagnetic field acts upon the polar parts of the EPS matrix via vibration energy was suggested to be comparable to other research efforts using ultrasonic frequencies to kill biofilms [78][79][80]. Caubet admits that at the time of reporting, attempts to model both the mechanical structure of and electric fields within biofilms were insufficiently well developed to yield any quantitative results from experimental data [29].…”
Section: The Bioelectric Effectmentioning
confidence: 79%
“…This would seemingly follow previous theories surrounding a charged EPS matrix [23,35] by suggesting that structural changes to the biofilm enhancing its susceptibility to antimicrobials are related to both mechanical and electrical characteristics. The way in which an electromagnetic field acts upon the polar parts of the EPS matrix via vibration energy was suggested to be comparable to other research efforts using ultrasonic frequencies to kill biofilms [78][79][80]. Caubet admits that at the time of reporting, attempts to model both the mechanical structure of and electric fields within biofilms were insufficiently well developed to yield any quantitative results from experimental data [29].…”
Section: The Bioelectric Effectmentioning
confidence: 79%
“…Chemotherapy-Rediske et al showed that ultrasound increased the killing of bacteria both in planktonic suspension [196,197] and biofilm forms [198][199][200] in the presence of antibiotics. This synergistic killing effect was most pronounced at lower frequencies and decreased as the frequency of insonation increased [201,202].…”
Section: Antibacterialmentioning
confidence: 99%
“…Our previous research showed that ultrasound enhanced the activity of aminoglycosides against Gram-negative bacteria in both planktonic and biofilm phenotypes (6,(13)(14)(15)(16)(17)(18). Ultrasound also increased killing of Gram-positive S. epidermidis and Streptococcus mitis by ampicillin (16).…”
Section: Introductionmentioning
confidence: 99%